1977
DOI: 10.1084/jem.145.3.523
|View full text |Cite
|
Sign up to set email alerts
|

Joint recognition by cytotoxic T cells of inactivated Sendai virus and products of the major histocompatibility complex.

Abstract: Cytotoxic T cells specific for Sendai virus were generated by culturing murine spleen cells in vitro together with UV-inactivated Sendai virus. In vivo immunization of donor mice with UV-inactivated Sendai virus resulted in an in vitro secondary response of increased magnitude. Cytotoxic activity was demonstrated in a short-term 51Cr-release assay, using syngeneic tumor cells which had been coated with inactivated Sendai virus by incubation at 4 degrees C for 30 min. The lysis of Sendai virus-coated target cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
2

Year Published

1977
1977
1981
1981

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(38 citation statements)
references
References 35 publications
5
31
2
Order By: Relevance
“…It has also been demonstrated that active infection is not required for the induction of a CTL response to Sendai virus (25). However, sensitization of uninfected targets does not occur with UV-inactivated influenza virus (26), and other investigators suggested that synthesis of early viral proteins is needed for lysis of vaccinia-or ectromelia-infected targets (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been demonstrated that active infection is not required for the induction of a CTL response to Sendai virus (25). However, sensitization of uninfected targets does not occur with UV-inactivated influenza virus (26), and other investigators suggested that synthesis of early viral proteins is needed for lysis of vaccinia-or ectromelia-infected targets (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…Spleen cells (7 X 106) were cultured in vttro for 5 days with 6 X 106 x-irradiated spleen stimulator cells as described (4). Virus-coated stimulator cells were prepared by a modification of the procedure described by Schrader and Edelman (5). After treatment with Tris/ NH4Cl and x-irradiation [1500 R (1 R = 2.58 X 10-4 C/kg), GE Maximar 250], 50 X 106 spleen cells were incubated with 0.01 ml of virus suspension for 90 min in 2 ml of culture medium and then washed to remove free virus particles.…”
Section: Methodsmentioning
confidence: 99%
“…Extensive experiments with five mutants of the H-2K b region and ectromelia, vaccinia, and lymphocytic choriomeningitis viruses (4,5,10,(14)(15)(16) have shown that a single gene in H-2K b, probably a cistron coding for an H-2 polypeptide antigen (17) makes an essential, direct contribution to the antigenic patterns recognized by Tc cells specific for H-2K ~ plus virus. Evidence from the H-2K b mutants (16) and recent work with Sendai virus (18) suggests that H-2 antigens become physically associated with viral antigens in infected cell membranes, but the way this happens is unclear. Therefore, another important feature of H-2 antigens may be their capacity to form compound or interaction antigens by associating with viral gene products (5,6,16,19,20).…”
mentioning
confidence: 99%